Identification of Candida Species on The Skin of Diabetes Mellitus Patients - Al Hafiz, OK. Muhammad; Amelia, Rina; Jusuf, Nelva Karmila (Sumatera Medical Journal, 2018)
Intertriginous candidiasis is a type of candidiasis which the lesion lies in the folds of the armpit, groin, intergluteal, folding of the breast, between the fingers or the toes, glans penis, and the umbilicus. One of the risk factors for intertriginous candidiasis is diabetes mellitus (DM). DM is a typical clinical syndrome characterized by the presence of hyperglycemia which is caused by deficiency or the decrease of insulin effectivity. Fungal infection of the skin with Candida species becomes easier in patients with immunocompromised conditions such as DM patients. Objective: To identify the Candida species in DM patient's skin. Method: This research is an observational descriptive study with cross sectional design. This research identifies Candida species from 30 DM patients at The Public Health Center Sentosa Baru Medan who met the inclusion and exclusion criteria by skin scraping with KOH 10% and slide culture. Results: The location of the rash was found in the crotch folds 63.3% and in the intergluteal 36.7%. All samples (100%) showed positive fungus structure with KOH 10% examination. On the examination of slide culture with Saboraoud Dextrose Agar media and identification of slide colony with Corn Meal Agar medium as many as 60% Candida spesies was found with overall species are Candida albicans.